THE INFLUENCE OF 1000 HPK VIDEO MEDIA ON INCREASING THE KNOWLEDGE AND ATTITUDE OF MOTHERS OF REPRODUCTIVE AGE COUPLES AS AN EFFORT TO PREVENT STUNTING IN GUGUK PANJANG HEALTH CENTER - Khadijah, Siti; Evareny, Lisma; Fadira, Elsa; Syuhada, Silvy; Zahara, Siti; Jannah, Zahra Tul (Jurnal Kesehatan - STIKes Prima Nusantara, 2024)
Background: There are many growth and development problems that occur in children, including stunting. Stunting is a condition of growth failure in children under five due to chronic malnutrition so that children are too short for their age. Malnutrition occurs from the time the baby is in the womb and in the early period after the baby is born, however, stunting conditions are only visible after the baby is 2 years old. Thus the period of 1000 HPK should receive special attention because it determines the growth rate of physique, intelligence, and productivity in the future. In 2020, the national stunting prevalence rate was 27.6%. In Bukittinggi city, the stunting rate in 2021 is 19%. This figure is still far from the national target for 2024 to 14%. Given the importance of stunting prevention, researchers are interested in conducting research on the Influence of 1000 HPK Video Media on Increasing Knowledge and Attitudes of Uisa Subur Couples as Stunting Prevention Efforts at the Guguk Panjang Health Center.Purpose: To determine the influence of health promotion media videos about 1000 HPK on increasing knowledge and changing attitudes of mothers of couples of childbearing age as an effort to reduce the incidence of stuntingMethods: This study is a quasi-experimental study, which uses a one-group pre-test post test design, with a sample of 18 people in the Guguk Panjang Health Center work area.Results: The results showed that before being given education through video media about 1000 HPK, the average maternal knowledge was 7.44 and after it was carried out it became 9.61. The average attitude of mothers before being given education was 34.88 and after it was carried out it was 37.88.Conclusion: There is an influence of 1000 HPK video media education as an effort to prevent stunting on increasing the knowledge and attitudes of mothers of couples of childbearing age at the Guguk Panjang health center..